2001
DOI: 10.1073/pnas.121180498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen on growth plate senescence and epiphyseal fusion

Abstract: Estrogen is critical for epiphyseal fusion in both young men and women. In this study, we explored the cellular mechanisms by which estrogen causes this phenomenon. Juvenile ovariectomized female rabbits received either 70 g/kg estradiol cypionate or vehicle i.m. once a week. Growth plates from the proximal tibia, distal tibia, and distal femur were analyzed after 2, 4, 6, or 8 weeks of treatment. In vehicle-treated animals, there was a gradual senescent decline in tibial growth rate, rate of chondrocyte proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
205
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(222 citation statements)
references
References 45 publications
(46 reference statements)
9
205
2
6
Order By: Relevance
“…Rather, it is estrogen that, by enhancing osteogenesis at the expense of chondrogenesis, accelerates the epiphyseal fusion rate and terminates linear growth (Cutler 1997). Furthermore, in a study in rabbits, Weise et al (2001) suggested that epiphyseal fusion is triggered when the proliferative potential of growth plate chondrocytes is exhausted, and that estrogen accelerates the programmed senescence of the growth plate, thereby causing earlier epiphyseal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is estrogen that, by enhancing osteogenesis at the expense of chondrogenesis, accelerates the epiphyseal fusion rate and terminates linear growth (Cutler 1997). Furthermore, in a study in rabbits, Weise et al (2001) suggested that epiphyseal fusion is triggered when the proliferative potential of growth plate chondrocytes is exhausted, and that estrogen accelerates the programmed senescence of the growth plate, thereby causing earlier epiphyseal fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Düşük dozlarda büyümeyi uyarırken, yük-sek dozlarda büyümeyi baskılamaktadır (11)(12)(13)(14)(15) . Yüksek doz östrojen, kısmen epifiz füzyonu üzerine direkt etkisiyle, kısmen de büyüme hormonu antagonisti gibi davranarak büyümeyi kısıtlar (16)(17)(18)(19) . Turner sendromlu olgularda gonadal yetersizliğe bağlı olarak östrojen düzeyleri düşük saptanır ve bu olguların çoğu östrojen tedavisi olmaksızın puberteye girememektedir.…”
Section: Frequency Of Osteoporosis In Children With Turner Syndrome Aunclassified
“…The epiphyseal growth plate's fate is to be resorbed after the pubertal growth spurt, at the time of sexual maturation [37]. The resorption and fusion of the growth plate follow the cessation of growth and are regulated by both systemic mechanisms (ie oestrogen hormone) and local mechanisms, intrinsic to the growth plate [38,39].…”
Section: The Polarization Of the Epiphyseal Growth Platementioning
confidence: 99%
“…It has been described that the growth plate chondrocytes have a finite proliferative capacity [39]. Therefore, the fusion of the growth plate is triggered when the proliferative potential of the chondrocytes is exhausted and finally all the remaining chondrocytes are replaced by bone, in which the epiphysis fuses with the metaphysic [37].…”
Section: The Polarization Of the Epiphyseal Growth Platementioning
confidence: 99%